Negotiating the Uniform: Youth Attitudes towards Military Service in Israel. (June 2019) - Girsh, Yaron
Military service is one of the key milestones in Jewish Israelis' transition to adulthood. Given the dominant role of the military in Israeli society, an understanding of young adults' attitude towards the importance of the military and the nature of their service is needed. Based on 44 group interviews with 132 Jewish Israeli high school students, the study follows the differential attitude of youths towards compulsory military service, along socioeconomic lines. It concludes that (a) despite changes in Israeli society, young people still consider soldiers as the ultimate models of heroism, and view military service as a necessary component of normative citizenship and (b) they negotiate the nature and content of their military service based on its expected contribution to future mobility opportunities. The findings indicate that within the shared cultural script of the military's importance, alternative paths play out without directly challenging the dominant consensus within Israeli society.